A techno-economic analysis based upon a parametric study of alkali-catalysed biodiesel production from feedstocks with high free fatty acid and water contents. Issue 4 (25th March 2022) - Al-Saadi, Luma Shihab; Eze, Valentine C.; Harvey, Adam P.
Abstract: TEAs (Techno-economic Analyses) were performed for various conditions for one-step homogeneous base catalysis of refined and low-grade vegetable oils containing moderate to high free fatty acids (FFAs) and water. The conditions modelled were based upon a "Design of experiments" study of the reaction using a meso-OBR, a continuous process screening device to rapidly screen through conditions. For refined rapeseed oil, 99% conversion to FAME was achieved at 13:1 methanol-to-oil molar ratio, 0.5 wt. % of catalyst, 50 °C and 16 min. For low-grade RSO (2.75 wt.% FFA) up to 90%, FAME was attained at 18:1 methanol-to-oil molar ratio, 2 wt% catalyst, 50 °C and 4.25 min. The TEAs were based on plant capacities of 100, 000 te/y, assuming a 20 yr plant lifetime. The outputs were compared to the conventional one-step biodiesel process and a two-step process for high FFA feedstock involving a pre-treatment step to reduce FFA content, followed by alkali-catalysed transesterification. The single-step process for low quality RSO at conditions identified here, which was significantly more economically viable than the conventional process using refined oil and the two-step process using waste cooking oil.